Overcoming the effects of intentional forgetting. - Lehman, Melissa; Malmberg, Kenneth (Memory & Cognition, 2011)
The long-term effects of the compartmentalization of task-irrelevant memories were investigated using a directed forgetting procedure. Many models tacitly assume the persistence of the costs and benefits of directed forgetting or otherwise fail to predict what factors might reduce or eliminate them. In contrast, a retrieving effectively from memory model (REM; Lehman & Malmberg, ) predicts that intentional forgetting should only be observed for free recall when temporal context is used to probe memory. By manipulating whether study lists were constructed from category exemplars or from a random set of words, and by either providing temporal or category cues at test, we tested the prediction. The effects of directed forgetting were eliminated when categorized lists were studied and category cues were provided. When categorized lists were used but category cues were not provided, the usual costs and benefits of directed forgetting were observed. These results specify the conditions under which the consequences of intentional forgetting can be overcome.